Estimation of Node Cache Occupancy in Satellite Storage Network - Erbao Wang (IEEE Access, 2021)
The satellite network with cache function becomes the future development trend. How to efficiently use the node cache of the satellite network has become a research hotspot. A theoretical problem that needs to be solved in the latest research on effective utilization of cache is the estimation of cache occupancy. Based on the martingale encapsulation theory, combined with the channel conditions, access protocols, and queuing strategies in the satellite storage network, a satellite node occupancy estimation method and theoretical bounds are proposed in a two-layer satellite network of GEO and LEO. The accuracy of the martingale encapsulation method in estimating the cache occupancy is estimated by simulations. The simulation results show that our method is precise. The cache occupancy estimation method we proposed provides a theoretical basis for the optimal allocation of satellite cache resources.